Development of a novel medium to improve the performance of Biological Aerated Filters (BAFs) - Moore, Rebecca Ellen (Cranfield University, 1999)
A foamed clay, StarLight C, was selected as a potential BAF medium after qualifying as a filter medium according to the BEWA standard tests, and showing the propensity to collect a biofilm. At loading rates > 10 kg COD/ m3 working volume/ d, two pilot- scale downflow BAFs running in parallel and containing either StarLight C or medium A (a standard expanded clay) achieved a mean of 87% suspended solids removal and 75% soluble COD removal. Both reactors were backwashed daily for ten minutes at a liquid flow rate corresponding to 40% of the minimum fluidisation velocity (Vmf) of the media. The approximate experimental Vmf of StarLight C was 120 m/h compared to 215 m/h for medium A. Therefore, the BAF using StarLight C exhibited between 11 and 19 % increased productivity at liquid velocities from 1.4 to 2.4 m/h. Lowering the Vmf of a BAF medium should also reduce the operating and capital costs of the process. According to representatives of the wastewater treatment companies, high operating costs are the major disadvantage of the BAF process. Increasing the feed bentonite concentration from 35 g/1 to 56 g/1 produced a StarLight C variant with improved crush resistance and a lower attrition rate. Meanwhile, a larger extruder nozzle was used to increase the particle size of the medium. Pilot-scale trials showed that the maximum run times were extended by between 8 and 31 hours when using the larger variant (2.5-4.5 mm diameter) compared to the smaller (1.5-3.5 mm diameter). Observing logarithmic head loss development and the cessation of suspended solids removal in the lower region of the reactor, suggested that the smaller StarLight C was an inefficient filter medium. Using an environmental scanning electron microscope, hydrated biofilms were observed growing on StarLight C’s surface. The highly variable biofilm distribution and structure is not accounted for by current biofilm and mechanistic process models. A first-order empirical model described the removal of soluble COD in the top section of the reactors containing medium A, small StarLight C and large StarLight C. The first-order constants were dependant on the liquid velocity and at 1.4 m/h were 61 d"1, 45 d'1 and 33 d"1 respectively.